Daisy comes home - Brett, Jan, 1949- (New York : Puffin Books, 2005)
Mei Mei's six hens are the happiest in China, but when Daisy--the smallest--falls into the river in a basket and drifts away, she must learn to survive on her own.
Wilson's Children
School Library Journal
Booklist starred
3.7
K-3
Keywords: Chickens -- Fiction; China -- Fiction; Chickens -- Fiction; China -- Fiction